Bagworm and red palm weevil—major pest and potential threat to the Malaysian oil palm industry - Syari Bin Jamian, Syari; Siti Izera Binti Ismail, Siti Izera; Sumaiyah Binti Abdullah, Sumaiyah; Nur Azura Binti Adam, Nur Azura; Zulkefli, Muhamad Haziq Hadif; Mohd Masri, Mohamed Mazmira (Springer Nature, 2024)
Elaeis gunineensis is the golden crop of Malaysia that contributes to the economic export of the country and the planters’ livelihood. Despite control measures to overcome the issue, bagworm remains the most reported infesting oil palm cultivation in the last four decades.